Peningkatan Kompetensi Guru melalui Pelatihan Pembuatan Media Pembelajaran ICT Berbasis Canva di MI Islahul Ummah Pranti Sedati Sidoarjo - Sasmita, Febriarsita Eka; Chumairoh, Ananda; Safiani, Aulia Mufidatus (Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PKM) activity was motivated by the low competence of teachers in designing ICT-based learning media, especially the use of the Canva application at MI Islahul Ummah Pranti Sedati Sidoarjo. This problem is caused by the generation gap and the limited digital literacy of senior teachers. The purpose of this activity is to improve teachers' skills in utilizing technology through training in creating ICT-based learning media using Canva. The activity was carried out using the Participatory Rural Appraisal (PRA) method which includes needs analysis, intensive training, practical assistance, and evaluation. The contribution of this activity lies in empowering teachers to be able to produce digital teaching media independently and foster a culture of digital literacy in the school environment. The evaluation results showed that 100% of participants succeeded in creating at least one digital teaching media, 70% of teachers were able to create two or more different designs, and 85% of participants reported increased confidence in using learning technology. These findings indicate that Canva-based training is effective in improving teacher competence in integrating technology into the teaching and learning process. Keywords: Learning Media, Canva, Community Service.